Efeito de diferentes regimes hídricos no solo sobre a produção e componentes da produção do feijoeiro (Phaseolus vulgaris L.) - Pinto, José Maria; Ferreira, Paulo Afonso; Bernardo, Salassier; Caixeta, Tarcísio José; Reis Condé, Alcides; Resende Monteiro, Marco Antônio (Revista Ceres, 2025)
A set of columns was used to determine the consumptive use of water and to measure the production and production components of the legume, Phaseolus vulgaris L., under protected conditions in which a transparent plastic cover was employed.